The relocation of cinema - Francesco Casetti (NECSUS, 2012)
In October 2011, the British artist Tacita Dean presented her work FILM at the Tate Modern in London. Dean’s installation is a film short projected in a continuous loop onto a large screen in a dark space furnished with seats for visitors. The written explication at the entrance to the room draws attention to the presence of all these elements: ‘35mm colour and black and white portrait format anamorphic film with hand tinted sequences, mute, continuous loop, 11 minutes. Large front projection; projection booth; free standing screen; loop system; seating.’ In her article in the Guardian, Charlotte Higgins described FILM as ‘pay[ing] homage to a dying medium’. In addition, FILM is undoubtedly an act in defense of film stock – that same film stock which Kodak announced (on 22 June 2009) it would cease to manufacture after 74 years of production, due to a steep decline in sales.